2021
DOI: 10.1177/01445987211013538
|View full text |Cite
|
Sign up to set email alerts
|

Influence rules and mechanisms of mechanical vibration at different frequencies on dynamic process of gas diffusion from coal particles

Abstract: To study the influence of vibration on gas desorption and diffusion in particle coal, gas desorption experiments on soft coal with outburst risk under different frequency vibrations were carried out by using a self-designed gas adsorption and desorption platform under vibration conditions, and the influence of different frequency vibrations on the diffusion kinetic parameters was quantitatively analyzed by using a dynamic diffusion coefficient model. The influence mechanism of vibration on gas desorption and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…17 From the free surface to the inside, it is pressure unloading zone, stress concentration zone, and original rock stress zone in order, and the risk of coal outburst within the pressure relief zone has been eliminated. [18][19][20][21] Zhang et al 22 studied the coal pillar failure mechanism; the results indicated that the coal pillar can be divided into broken zone, stable zone, and collapsed zone, in which the stabilized zone accounts for one-third of the coal pillar width and plays a decisive role in coal pillar failure. Shi et al 23 investigated the movement law, the failure mechanism and the fracture evolution law of goaf-side entry driving in thick coal seams through experiments and numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 From the free surface to the inside, it is pressure unloading zone, stress concentration zone, and original rock stress zone in order, and the risk of coal outburst within the pressure relief zone has been eliminated. [18][19][20][21] Zhang et al 22 studied the coal pillar failure mechanism; the results indicated that the coal pillar can be divided into broken zone, stable zone, and collapsed zone, in which the stabilized zone accounts for one-third of the coal pillar width and plays a decisive role in coal pillar failure. Shi et al 23 investigated the movement law, the failure mechanism and the fracture evolution law of goaf-side entry driving in thick coal seams through experiments and numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Mining pressure theory shows that, under the influence of mining operation, the roof stress will be redistributed 17 . From the free surface to the inside, it is pressure unloading zone, stress concentration zone, and original rock stress zone in order, and the risk of coal outburst within the pressure relief zone has been eliminated 18–21 . Zhang et al 22 studied the coal pillar failure mechanism; the results indicated that the coal pillar can be divided into broken zone, stable zone, and collapsed zone, in which the stabilized zone accounts for one‐third of the coal pillar width and plays a decisive role in coal pillar failure.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of gas desorption excited by vibration wave, Chen et al [18,19] studied the influence of vibration on gas desorption diffusion in granular coal and drew the following conclusions: (1) With the increase of vibration frequency, gas desorption of coal samples first increased and then decreased. (2) Mechanical vibration could generate shear force in adsorbed gas to promote its desorption.…”
Section: Introductionmentioning
confidence: 99%